Bank credit risk and macro-prudential policies: Role of counter-cyclical capital buffer - Benbouzid, Nadia; Kumar, Abhishek; Mallick, Sushanta K.; Sousa, Ricardo M.; Stojanovic, Aleksandar (Journal of Financial Stability, 2022)
This paper investigates the impact of macro-prudential policy (proxied by the counter-cyclical capital buffer (CCyB)) on bank credit risk during uncertain times, as banking sector stability is crucial in promoting financial intermediation. Using a unique daily data set consisting of 4939 credit default swaps (CDS) of 70 banks from 25 countries over the period 2010–2019, we find that CCyB tightening decreases bank-level CDS spreads, while CCyB loosening increases CDS spreads. This heterogeneous effect of CCyB arises due to its asymmetric effect on the capital ratio (i.e., the equity-to-total assets ratio) of banks. Tightening CCyB significantly increases capital, whereas loosening CCyB does not impact capital. Thus, the risks that emanate from the banking sector during periods of heightened uncertainty and financial distress can be significantly dampened when CCyB regulation is enabled. Consequently, macro-prudential policies for banks to hold higher levels of capital during good times are justified to contain financial market risks during downturns.